Multi-Sensory Marketing and Impulsive Buying Behavior: The Role of Impulsive Buying Traits - Le, Nguyen; Mai, Ngoc Thi Bich; Nguyen, Nhu Y Thi; Vu, Huyen Ngoc Thi (Emerging Science Journal, 2024)
The rapid growth of the retail market, coupled with increased consumer income, has led to a surge in impulsive and unplanned shopping. This study aims to examine the relationships between multi-sensory marketing, customers' moods, impulsive buying traits, and impulsive buying behavior, using the Stimulus-Organism-Response (S-O-R) model. Customers' mood acts as a mediator and impulsive buying traits as a moderator. The researchers surveyed 450 consumers in Vietnam using the method of non-probability sampling and analyzed the data using SPSS and Smart PLS 4.0. The results show that customers' moods and impulsive buying traits positively influence impulsive buying behavior, with impulsive buying traits also significantly moderating the relationship between mood and impulsive buying. Additionally, customers' moods mediate the relationship between multi-sensory marketing and impulsive buying behavior. This research fills gaps in previous research by incorporating multi-sensory marketing and impulsive buying traits as variables and provides managerial implications for businesses and retailers to develop effective marketing strategies to encourage impulsive purchases and increase sales. Academically, the research reaffirms the relevance of the S-O-R model in the retail context and paves the way for future investigations into consumers' impulsive buying behavior. Doi: 10.28991/ESJ-2024-08-05-05 Full Text: PDF